2015
DOI: 10.1149/2.0691602jes
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Upper Cutoff Potential on LaPO4-Coated and Uncoated Li[Ni0.42Mn0.42Co0.16]O2/Graphite Pouch Cells

Abstract: Li [Ni 0.42 Mn 0.42 Co 0.16 ]O 2 /graphite pouch cells, with and without a LaPO 4 coating on the positive electrode active material, containing the additives prop-1-ene-1,3-sultone, 1,3,2-dioxathiolane-2,2-dioxide and tris-(trimethyl-silyl) phosphite were studied using chargehold-discharge cycling experiments up to potentials between 4.4 and 4.5 V at 40 • C. Simultaneous electrochemical impedance spectroscopy measurements were made during cycling. The effects of a 24 hour hold at the top of charge at upper cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
65
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 21 publications
1
65
0
1
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26][27] Such results cannot be simply extrapolated to full cells especially when electrolyte additives are used. For example, J. Xia et al 28 and K.J Nelson et al 29 showed that LaPO 4 typically has large secondary particles around 15 μm made of agglomerates of small crystals of ∼200-400 nm. For Al 2 O 3 coated NMC532 (AC-532), Al 2 O 3 particles are usually around 40 nm scattered on the surface of the NMC532 particles.…”
mentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27] Such results cannot be simply extrapolated to full cells especially when electrolyte additives are used. For example, J. Xia et al 28 and K.J Nelson et al 29 showed that LaPO 4 typically has large secondary particles around 15 μm made of agglomerates of small crystals of ∼200-400 nm. For Al 2 O 3 coated NMC532 (AC-532), Al 2 O 3 particles are usually around 40 nm scattered on the surface of the NMC532 particles.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22] Ma et al and Nelson et al found that a ternary additive combination can greatly improve NMC442/graphite cell performance at high voltage. [11][12][13] Xia et al reported that fluorinated electrolyte and ECfree electrolyte also enhance NMC/graphite cell performance. [16][17][18][19] Another approach to improve cell stability is the application of an inorganic coating onto the NMC surface.…”
mentioning
confidence: 99%
“…Useful electrolyte additives include triallyl phosphate (TAP), 21 pyridine boron trifluoride (PBF) [22][23][24] and a mixture of additives containing prop-1-ene-1,3-sultone (PES), tris-(trimethylsilyl) phosphite (TTSPi) and 1,3,2-dioxathiolane-2,2-dioxide (DTD) or methylene methyldisulfonate (MMDS). [16][17][18]25,26 Mixtures with 2 wt% PES + 2 wt% TTSPi + 2 wt% DTD or 2 wt% PES + 1 wt% TTSPi + 1 wt% MMDS in the control electrolyte (1 M LiPF 6 ethylene carbonate (EC): ethyl methyl carbonate (EMC) 3:7 w:w electrolyte) are called PES222 or PES211in this report, respectively. The use of surface coatings at the positive electrode is another effective way to enhance high voltage cell performance.…”
mentioning
confidence: 99%
“…Nelson et al found that LaPO 4 -coated NMC442/graphite pouch cells with PES222 had worse cell performance than uncoated NMC442/graphite pouch cells with PES222. 17 Even though the effects of surface coatings have been extensively studied, the mechanism of function of positive electrode surface coat- * Electrochemical Society Fellow.…”
mentioning
confidence: 99%